Impact of UTAUT predictors on the intention and usage of electronic health records and telemedicine from the perspective of clinical staffs - Venugopal, P. (2019)
Technology adoption play significant role for good healthcare services. It is very important to understand and identify the requirements and perceptions of hospital employees for the implementation of technology in their work place. This study determines the impact of performance expectancy, effort expectancy and social influence on behavioural intention as well as the impact of facilitating conditions on technical/clinical staff’s perspective. The structured questionnaire is administered to 770 clinical staffs on the usage of telemedicine and electronic health records in hospitals. A valid sample of 568 was returned back for further analysis. Regression analysis using AMOS 20 is performed to examine the effect of the constructs. Findings revealed that performance expectancy, effort expectancy, and social influence have a significant impact on behavioural intention and facilitating condition also significantly impacts behavioural intention which in turn impacts usage behaviour of electronic health records and telemedicine. The limitations and future research are suggested and delineated.